2016
DOI: 10.1016/j.physbeh.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Daily feeding regimen impacts pig growth and behavior

Abstract: A primary swine production goal is to increase efficiency of lean tissue gains. While many swine production systems currently utilize ad libitum feeding, recent research suggests that altering feeding patterns may impact feed efficiency. Therefore, the objective of this study was to compare two feeding patterns and evaluate their impact on whole body tissue accretion, feeding behavior and activity in growing pigs. Forty eight individually housed gilts (55.9±5.2kg on test BW) were assigned into one of two feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…Ramaekers et al (1996) also found that restricting diets to 18 MJ ME above the daily energy requirement for maintenance resulted in an increase in lean and a decrease in fat. These results are also supported by Colpoys et al (2016), who in a 7-wk study with gilts allowing the pigs access to the feeder either for 2 periods of 1 h daily (2 times) or ad libitum found that the pigs fed ad libitum had an increased growth rate, increased feed intake (8%), and an increased fat and lean tissue accretion rate compared to those fed twice daily. Davies et al (1980) found that pigs on a high plane of nutrition had more fat than those on a low plane of nutrition.…”
Section: Discussionsupporting
confidence: 61%
“…Ramaekers et al (1996) also found that restricting diets to 18 MJ ME above the daily energy requirement for maintenance resulted in an increase in lean and a decrease in fat. These results are also supported by Colpoys et al (2016), who in a 7-wk study with gilts allowing the pigs access to the feeder either for 2 periods of 1 h daily (2 times) or ad libitum found that the pigs fed ad libitum had an increased growth rate, increased feed intake (8%), and an increased fat and lean tissue accretion rate compared to those fed twice daily. Davies et al (1980) found that pigs on a high plane of nutrition had more fat than those on a low plane of nutrition.…”
Section: Discussionsupporting
confidence: 61%
“…Whole body, bone, and lean tissue mass, and fat mass and percentage were provided by the raw DXA scans. Data from the raw DXA output was then adjusted to account for blood volume and gut fill using calibration curves that were built as previously described (Colpoys et al, 2016;Curry et al, 2017). These longitudinal scan data were then used to calculate tissue accretion rates (g/d) from corrected DXA scan results using the following formula: g/d = (corrected final scan measurement -corrected initial scan measurement) days between scans…”
Section: Whole Body Composition and Tissue Accretion Ratesmentioning
confidence: 99%
“…It has been shown that rats trained to eat their daily ration in a minimal time had greater lipogenesis and gained more body fat than nibbling rats (Cohn, 1963). The conclusions will obviously not be valid, if the snacking strategy is associated with greater total feed intake (Colpoys et al, 2016), thus resulting in opposite differences in body composition. In the simulations presented in Fig.…”
Section: Variations In the Frequency Of Glucose Availabilitymentioning
confidence: 99%
“…The feeding strategy is important in animal production, where a primary goal is to increase efficiency of lean tissue gains. Caution must be taken to simply extrapolate results from the cellular scale to the whole-animal level, as other factors such as physical activity, stress, and therefore energy expenditure can affect the results (Colpoys et al, 2016;Le Naou, 2014) that are not accounted for in the present framework. …”
Section: Variations In the Frequency Of Glucose Availabilitymentioning
confidence: 99%